Bioactive components derived from bovine milk - Lisak Jakopović, Katarina (Array, 2019)
In recent years, functional foods and bioactive components in foods have drawn a lot of attention as well as interest of food scientists, nutritionists, health professionals, and consumers. The advent of this new food category has been facilitated by increasing scientific knowledge about the metabolic and genomic effects of diet and specific dietary components on human health. The relationship between health and diet is well known and it is a main key for prevention of variety of diseases. Milk is considered as a very good source of bioactive components and it has been known to contain macro- as well as micronutrients of high nutritional and therapeutic value. Also, bioactive components have been exploited from milk and dairy products for application in functional foods and for potential pharmaceutical use. Biologically active compounds guard neonates and adults against pathogens and illnesses. Some major bioactive components of milk are derived from caseins, whey proteins, lipids, lactoferrine, vitamins, immunoglobulins and growth factors. The aim of this paper was to provide an overview and explain the health effects of already known and recently detected bioactive components derived from bovine milk on humans.